Literacy Profile of Flood and Rob Disaster Mitigation Among Sciences Teachers in Central Java - Roshayanti, Fenny; Siska Pramasdyahsari, Agnita; Burhanudin, Aan; Ha, Minsu (KnE Social Sciences, 2024)
There is a need to acquire the data description of science teachers regarding literacy mitigation in Central Java. However, there is no specific data that informs these conditions. Therefore, the research aims to identify the literacy of flood disaster mitigation among science teachers in the Central Java province. Several 125 science teachers from 6 districts/cities in Central Java were involved as respondents. The flood and tidal disaster literacy instrument consists of 17 items divided into 2 parts. The first part concerns the teacher’s knowledge of floods and tidal waves. The second part contains the teacher’s insights about mitigating flood and tidal disasters. The findings show that the average teacher’s knowledge about floods and tidal waves is good (8.4 of 10). Meanwhile, the average knowledge of science teachers regarding literacy of flood and tidal disaster mitigation is in the sufficient category (11.4 of 18). This fact shows that science teachers’ flood and disaster mitigation literacy needs to be improved. Instilling disaster mitigation literacy, especially floods and tidal waves, can be done by implementing disaster mitigation education in science learning through research and community service. Keywords: mitigation literacy, disaster mitigation, STEAM, early warning system